Evaluation of The Effectiveness of Digital-Based PAI Learning in Secondary Education Using The CIPP Stufflebeam Model Approach - Febrino, Febrino; Iskandi, Iskandi (Journal of Educational Sciences, 2026)
The use of digital media in learning has the potential to enhance interactivity, students’ understanding, and learning motivation. However, the implementation of digital-based Islamic Religious Education (PAI) learning at the secondary education level in the Bangka Belitung Islands still faces various challenges. This study aims to evaluate the effectiveness of digital-based PAI learning using the Stufflebeam CIPP evaluation model, which includes context, input, process, and product aspects. A qualitative approach with a case study method was employed in 20 senior high schools, vocational schools, madrasahs, and Islamic boarding schools through observations, interviews with teachers and students, and document analysis. The findings indicate that digital-based PAI learning is relevant to national education policies; however, disparities exist in infrastructure availability and human resource readiness. Digital media enhances learning interactivity and students’ motivation, although its implementation has not yet been optimal. The study concludes that improving facilities and strengthening teachers’ digital competencies through continuous training are essential to enhance the effectiveness of digital-based PAI learning. and ongoing training for PAI teachers that is tailored to the needs of each evaluation aspect.